Oxyspirura petrowi infection leads to pathological consequences in Northern bobwhite (Colinus virginianus). Issue 3 (December 2016) - Dunham, Nicholas R.; Reed, Scott; Rollins, Dale; Kendall, Ronald J.
Abstract: Debilitating ocular diseases are often reported in avian species. By and large, helminth parasites have been overlooked in avian diseases and regarded as inconsequential. The decline of Northern bobwhite quail ( Colinus virginianus ) in the Rolling Plains ecoregion of Texas has prompted an investigation of the factors influencing their disappearance. Infection by the eyeworm ( Oxyspirura petrowi ) has been documented in many avian species; however, the effect it has on its host is not well understood. Heavy eyeworm infection has been documented in Northern bobwhites throughout this ecoregion, leading to eye pathology in this host species. The present study further documents and supports the pathological changes associated with O. petrowi in bobwhites. Graphical abstract: Highlights: O. petrowi infection caused adenitis in Northern bobwhites. Histological sections demonstrated lesions associated with O. petrowi infection. Corneas appeared to be cloudy and have early ulcerative erosions. Inflammation and glandular atrophy were associated with O. petrowi infection.